Peningkatan kemampuan kolaborasi siswa kelas VII pada materi operasi aljabar melalui pembelajaran TGT berbantuan game ular tangga - Nur Hikmah; Yenni Yenni; Sigit Raharjo (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
This study aims to examine the effectiveness of implementing the TGT model assisted by a snake and ladder game on enhancing seventh-grade students' collaborative abilities in algebraic operations material. A comparative method based on a quantitative approach was applied in this research. The research subjects involved 60 students. Research data were collected using collaboration ability questionnaires, activity observation sheets, and documentation. Data analysis techniques included prerequisite tests alongside inferential tests (t-tests and N-Gain analysis). The findings indicate a significant strengthening across all indicators of student collaboration within the experimental class. Based on the Independent Sample t-Test, a significance value of 0.000 < 0.05 was obtained, confirming a highly substantial difference. The N-Gain analysis reinforces these findings, showing that the experimental class achieved an index score of 0.66 (medium), whereas the control class only obtained a score of 0.24, (low). Substantively, the enhancement of students' collaboration skills in this study runs parallel with the development of meaningful mathematical reasoning. Accordingly, the TGT model based on the snake and ladder game proves effective in decentralizing the teacher's dominance and minimizing students' learning obstacles.